Cancer of the Pancreas: The Best Image for Early Detection – CT, MRI, PET or US? - Anthony E Hanbidge (Canadian Journal of Gastroenterology)
Pancreatic cancer has a poor prognosis, and the best chance for survival is to diagnose the tumour at an early stage. Abdominal ultrasound, computed tomography, magnetic resonance imaging and endoscopic retrograde cholangiopancreatography are the most commonly used radiological techniques for imaging the pancreas. The diagnostic evaluation should be tailored to the individual patient. Dual-phase helical computed tomography and magnetic resonance imaging have similar accuracies for detecting and staging pancreatic adenocarcinoma. Sonography results are highly dependent on the skill and persistence of the operator. No radiological examination is very sensitive at visualizing small metastases in the lymph nodes and peritoneum, or on the surface of the liver. Thus, it is difficult to establish with certainty whether a tumour is resectable. Another major challenge is to differentiate cancer from an inflammatory mass in chronic pancreatitis. Functional imaging (using positron emission tomography with fluorodeoxyglucose) may be helpful, especially if the images are fused with those of computed tomography or magnetic resonance imaging. The diagnostic accuracies, applications and limitations of the various modalities are discussed.